Peningkatan Motivasi Belajar PAK Melalui PBL pada Materi Pelestarian Lingkungan Kelas V - Adriana Maria Obenu; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This Classroom Action Research (CAR) was conducted to address the lack of student motivation in Catholic Religious Education (PAK) subjects, which often leads to low academic achievement. The study aimed to determine whether the application of the Problem Based Learning (PBL) model could improve students' learning motivation and academic performance, specifically in the topic